International Arbitration under debate - Narancio, Victoria (2017)
Is the choice of the arbitral seat still an important decision in international arbitration? Should arbitral awards be subject to greater judicial scrutiny? Should the appeal be in international arbitration? Is it possible that an annulled arbitral award is recognized under the New York Convention? Should the New York Convention be amended to achieve CNY 2.0? Is investment arbitration a system that works? Are the criticisms of investment arbitration valid? In this interview, Gary Born responds to each of these questions by addressing many controversial current issues in international arbitration.